2021
DOI: 10.1016/j.lungcan.2021.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Survival benefit of osimertinib combination therapy in patients with T790M-positive non-small-cell lung cancer refractory to osimertinib treatment

Abstract: Survival benefit of osimertinib combination therapy in patients with T790M-positive non-small-cell lung cancer refractory to osimertinib treatment Po-Lan Su (Conceptualization) (Data curation) (Investigation) (Methodology) (Writing -review and editing), Jeng-Shiuan Tsai (Conceptualization) (Data curation) (Investigation) (Methodology) (Writing -review and editing), Szu-Chun Yang (Data curation) (Writing -review and editing), Yi-Lin Wu (Data curation) (Writingreview and editing), Yau-Lin Tseng (Data curation) (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
(25 reference statements)
0
8
0
Order By: Relevance
“…The negative result presented may be caused by on-targeted resistance not taking into consideration. A retrospective study in T790M-positive osimertinib-refractory patients treated with osimertinib combined with chemotherapy yielded better OS than chemotherapy [119]. The same as IMPRESS study, the COMPEL study is to investigate continued osimertinib combined with chemotherapy versus mono-chemotherapy after first-line osimertinib progresses (NCT04765059) promisingly.…”
Section: Chemotherapy and Antiangiogenic Therapymentioning
confidence: 99%
“…The negative result presented may be caused by on-targeted resistance not taking into consideration. A retrospective study in T790M-positive osimertinib-refractory patients treated with osimertinib combined with chemotherapy yielded better OS than chemotherapy [119]. The same as IMPRESS study, the COMPEL study is to investigate continued osimertinib combined with chemotherapy versus mono-chemotherapy after first-line osimertinib progresses (NCT04765059) promisingly.…”
Section: Chemotherapy and Antiangiogenic Therapymentioning
confidence: 99%
“…Osimertinib ( Figure 1 ), is a standard first-line treatment option for patients with advanced EGFR T790 M-mutated NSCLC, effectively extending survival and improving patients’ life quality [ 6 , 7 ]. Subsequently, aumolertinib and furmonertinib ( Figure 1 ) were approved in China for treating advanced EGFR T790 M-mutated NSCLC.…”
Section: Introductionmentioning
confidence: 99%
“…Aside from targeted therapy, chemotherapy and the addition of antiangiogenic inhibitors to EGFR-TKI therapy after progression are also alternative strategies. Studies have shown that patients with resistance to osimertinib derived prolonged clinical benefits from the continuous use of osimertinib alone or in combination with radiotherapy or chemotherapy ( Le et al, 2018 ; Su et al, 2021 ; White et al, 2021 ). However, it has not been elucidated whether the combination of osimertinib and bevacizumab is beneficial after the progress of osimertinib.…”
Section: Discussionmentioning
confidence: 99%